Woman aged 42 years with Parkinson’s disease: a case study - Verma, Yachna (International Journal of Research in Medical Sciences, 2025)
Parkinson’s disease is also known as shaking palsy. It is a chronic, progressive neurodegenerative disease characterized by both motor and non-motor features. The prevalence of Parkinson disease is reported to be approximately 1% in people 60 years of age and older increases to 1% to 3% in the 80 plus age groups. Risk factors included oxidative stress, the formation of free radicals and environmental toxins. The most frequently reported symptoms in Parkinson disease are tremors in one hand, other symptoms showing slowness in movement, stiffness and loss of balance. Various diagnostic test performed to rule out Parkinson’s disease that is brain imaging, dopamine active transporter (DaT) scan, skin biopsy etc. Parkinson’s disease can be managed by combination of drugs like levodopa and monoamine oxidase (MAO)-B inhibitors.